Brahmaputraka Chheuchhau: Portrayal of the Indian Nepali Diasporic Life - Timalsina, Ramji (JODEM: Journal of Language and Literature, 2023)
This article analyses how Indian Nepali writer Lil Bahadur Chhetri’s novel Brahmaputraka Chheuchhau [Alongside the Brahmaputra] depicts the transnational life of the Nepali Diaspora in India. The analysis of the novel is based on the theory of diaspora and its literature discussed by Robin Cohen, James Clifford and Janine Dahinden. The analysis focuses on the setting, characterization, the migrants’ relation with the hostland mainstream, Nepali cultural practices and the role of the migrants in the development of the land of arrival. It finally presents the common features of the Nepali Diaspora in Assam, India. The discussion concludes that the novel is a good example of Nepali diasporic literature. It is hoped that this article can be a sample for the analysis of other works of Nepali diasporic creations, especially the works of fiction.